2014
DOI: 10.1186/1756-3305-7-172
|View full text |Cite
|
Sign up to set email alerts
|

Burchellin: study of bioactivity against Aedes aegypti

Abstract: BackgroundThe dengue mosquito Aedes aegypti Linnaeus, 1762 is a widespread insect pest of serious medical importance. Since no effective vaccine is available for treating dengue, the eradication or control of the main mosquito vector is regarded as essential. Since conventional insecticides have limited success, plants may be an alternative source of larvicidal agents, since they contain a rich source of bioactive chemicals. The aim of this study was to evaluate the larvicidal activity of the neolignan burchel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…However, the results reported here about O. quixos (LD99 = 181.89 ppm) are consistent with findings on Ocotea cymbarum, showing that its strongest toxic effect was 100% mortality in Ae. aegypti third age larvae at concentrations !30 ppm [23]. Previous studies on the monoterpene 1,8-cineole, which is the main constituent of O. quixos oil in this experiment, showed larvicidal activity toward the larvae of several mosquitos including Ae.…”
Section: Anti-larval Effects Of Essential Oilssupporting
confidence: 51%
“…However, the results reported here about O. quixos (LD99 = 181.89 ppm) are consistent with findings on Ocotea cymbarum, showing that its strongest toxic effect was 100% mortality in Ae. aegypti third age larvae at concentrations !30 ppm [23]. Previous studies on the monoterpene 1,8-cineole, which is the main constituent of O. quixos oil in this experiment, showed larvicidal activity toward the larvae of several mosquitos including Ae.…”
Section: Anti-larval Effects Of Essential Oilssupporting
confidence: 51%
“…Certain plant preparations are toxic to different mosquito species larvae 19–22 and have therefore been proposed to be alternatives to conventional larvicides. Active larvicidal constituents (LC 50 < 50 mg/L 39 ) derived from plants include alkaloids (e.g., retrofractamide A and three isobutylamides 40 , 0.004–0.86 mg/L), terpenoids (e.g., 9-oxoneoprocurcumenol and neoprocurcumenol 41 , 5.81 and 13.69 mg/L), coumarins (e.g., imperatorin and eight coumarins 26 , 2.88–44.39 mg/L), flavonoids (e.g., karanjin, karanjachromene, pongamol, and pongarotene 42 , 14.61–37.61 mg/L), phenylpropanoids (e.g., ethyl p -methoxycinnamate 43 , 12.3–20.7 mg/L), lignans (e.g., (−)-asarinin 25 , 10.49–16.49 mg/L), neolignans (e.g., burchellin 44 , 15.5 mg/L), cyanogenic glycosides (e.g., dhurrin 45 , 12 mg/L), lactones (e.g., butenolides 1 and 2 46 , 0.41 and 0.47 mg/L), acetylenic alcohols (e.g., falcarinol and falcarindiol 47 , 3.49 and 6.51 mg/L), and fatty acids (e.g., oleic acid and palmitic acid 42 , 18.07–18.45 and 34.50–42.96 mg/L). Kiran et al .…”
Section: Discussionmentioning
confidence: 99%
“…Histological tests were performed in accordance with the method of Narciso et al [19] with slight modifications. Larvae treated with different concentrations of bruceine A, 1 ppm of temefos, or distilled water were fixed in 2.5% glutaraldehyde in sodium cacodylate buffer (0.1 M, pH 7.4) for 4 h. Samples were then dehydrated in a gradient ethanol series (70%, 80%, 90% 96%, and 100%).…”
Section: Histological Testmentioning
confidence: 99%
“…Narciso et al [19] reported that histomorphological changes resulted from treatment with burchelin from Ocotea cymbarium caused the death of L3-L4 larvae of A. aegypti. The midgut epithelial cells of the larvae exhibited disorganization, damage, and vacuolization.…”
Section: Histological Changes Of a Aegypti (L) Larvaementioning
confidence: 99%